Physical clinical care and artificial-intelligence-guided core resistance training improve endurance and patient-reported outcomes in subjects with lower back pain. (March 2023) - Bates, Nathaniel A.; Huffman, Allison; Goodyear, Evelyn; Nagai, Takashi; Rigamonti, Luca; Breuer, Logan; Holmes, Benjamin D.; Schilaty, Nathan D.
Abstract: Background: Low back pain is an extremely prevalent issue with an extensive impact, ranging from decreased quality of life to lost years of productivity. Many interventions have been developed to alleviate chronic lower back pain, yet it remains a widespread problem. The objective of this study was to examine the role of artificial intelligence guided resistance training relative to clinical variables in subjects experiencing lower back pain. Methods: 69 out of 108 enrolled and 92 accrued subjects completed the 8-week intervention. Subjects were randomized into four groups (Control, Training, Clinical, or Combined). The Training cohort received supervised artificial-intelligence-guided core-focused resistance training while the Clinical group received clinical care. The Combined group received both clinical care and artificial-intelligence-guided training and the Control group received no treatment. Participants were evaluated using functional testing and patient-reported outcomes at baseline, 4 weeks, and 8 weeks. Findings: In the clinical tests, the Clinical and Combined cohorts showed increased total time for isometric extensor endurance and the Clinical cohort increased total distance traveled in the 6-min walk test at 8 weeks. The Training, Clinical, and Combined groups showed improvements in Patient-reported outcomes after 8 weeks. Most of the significant improvements were only seen at the 8-week evaluation for both the clinical evaluations and Patient-reported outcomes. The Control group did not show significant improvements in any outcome measures. Interpretation: The present data indicate that core-focused interventions, including artificial-intelligence-guided moderate-resistance exercise, can increase objective functional outcomes and patient satisfaction using Patient-reported outcomes in individuals with lower back pain. Highlights: Low back pain continues to be a major cost and disability burden on the medical community. Artificial intelligence guided exercise improved function and outcomes in low back pain patients. Control patients failed to exhibit improvements over the 8-week period. Artificial intelligence guided exercise offers a supplement to clinical care for low back pain.